PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK KELAS VII SMPN 2 2 X 11 KAYU TANAM TAHUN PELAJARAN 2018/2019 - Chelsi Ariati (Jurnal Edukasi dan Penelitian Matematika, 2019)
One of the mathematics learning goals thatexpected in junior high schools is that students have good reasoning skills. However, according to the results of the tests conducted at 2X11 Kayu Tanam showed low mathematical reasoning abilities of students. This could be improved byimplementing  discovery learning model. The purpose of this study was to describe the increase in mathematical reasoning abilities of students who learn with discovery models analyzeand describe whether mathematical reasoning abilities of students who learn with discovery learning learning models were better than mathematical reasoning abilities of students who learn with direct learning models in class VII 2X11 SMPN 2 Kayu Tanam. This research was a combination of quasy experiments and descriptive research with the research design The Nonequivalent Posttest-Only Control Group Design. Based on the results of tests and quizzes, it isfind that there is an increase in the ability of students who learn with discovery models. According to the results of the hypothesis test, the mathematical learning ability of students learning using discovery learning models is better than the mathematical learning abilities of students who learn with direct learning models. It can beconclude that the discovery model influences students' mathematical reasoning abilities.Keywords - Discovery^Learning Model, The Abilityof Mathematical^Reasoning